Partly cloudy ethics in war, espionage, covert action and interrogation - Perry, David L. 1959- (Scarecrow professional intelligence education ;, 2009)
Provides a practical approach to analyzing ethical issues in war and intelligence operations and applies careful reasoning to issues of vital importance today-- such as the question of torture in interrogating detainees, employing espionage to penetrate hostile regimes and terrorist cells, mounting covert action to undermine their power, using discrimination and proportionality in military operations, avoiding atrocities in combat and counterinsurgency, and cultivating moral wisdom